The effect of Layout in measuring customer satisfaction (patients) using (Servicescape) model - عبد الوهاب, نادية لطفي (Journal of Economics and Administrative Sciences, 2016)
Abstract:This research aims to identify the impact of the Layout Ghazi al-Hariri hospital for surgery specialist on customer satisfaction (patients) using the model (Servicescape), the problem of the research represented in the extent to which the hospital management design of the service and Layout hospital aesthetic and functional aspects that fit patients for therapeutic and nursing services , and used the developer scale by (Miles et al., 2012) for data collection, which includes the independent variable in (17) items distributed in three dimensions (Facility aesthetics , hospital cleanliness, and the Layout accessibility ) The dependent variable is the satisfaction of customers (patients) which includes 10 Items, and research involved patients admitted in different hospital departments and by 129 patients, were verified validity and reliability of the scale, and used several methods of statistical to get the results such as mean and standard deviation and test (Z) to see a significant correlation between the two variables and test ((F) test to know the moral of this influence and the use of statistical software (SPSS) version twenty one, The research found several conclusions from them, showing that there is an inconsistency between the colors of the walls and the floor, which is reflected on the aesthetics of the hospital and especially in the design of the Layout of the service task to be functional and attractive to customers (patients) at the same time, and that the hospital does not respect the exploitation of space this property hospital corridors to take advantage of them to break customers (patients) and thus places available to them to rest, and in particular they are of different pathological conditions, and recommended Find the need to pay particular attention to harmonically colors, especially the colors of the walls and floor of what for these aspects of the important implications of preferring to stay comfortable feeling to customers (patients) to try to take advantage of available spaces such as corridors to put comfortable chairs to sit sick while traveling inside the hospital to receive treatment services .